Factors Associated With Post-Stroke Self Efficacy - Fuji Istiana; Fitria Handayani; Muhamad Thohar Arifin (Media Keperawatan Indonesia, 2021)
One of the psychological problems experienced by stroke patients is self-efficacy. Stroke patients on average lack confidence in themselves to do exercises or activities that will have an impact on the recovery process of stroke patients. Several factors that vary related to low self-efficacy in stroke patients are one of the causes. The scoping review aims to identify factors related to self-efficacy in a post-stroke patient. The methods use a systematic review through review articles relevant to the topic from CINAHL database, MEDLINE, Academic search ultimate, science direct, and Taylor & Francis with a publication year spanning 2015 to 2020 and with the keyword “self-efficacy” and “stroke” then analyzed using a synthesis matrix. The inclusion criteria in this study were articles in English with longitudinal study design or cross-sectional study and self-efficacy as the dependent variable. The results of a review of four journals that met the inclusion criteria found factors related to self-efficacy in a post-stroke patient including depression, age, vascular history, fear, physical activity, Body Mass Index (BMI) and emotional function. The study concludes that depression, age, vascular history, fear, physical activity, Body Mass Index (BMI) and emotional function are factors related to self-efficacy in post-stroke patients. The factor most strongly associated with post-stroke patients self-efficacy is depression.